Protective effect of soluble Klotho in pediatric patients undergoing cardiac surgery with cardiopulmonary bypass support—A pilot study. Issue 10 (5th August 2021) - Pode Shakked, Naomi; Rosenblat, Orgad; Sagiv, Doron; Molad, Jeremy; Weinberg, Hagai; Shlomo, Meital; Tokatly Latzer, Itay; Pleniceanu, Oren; Mishali, David; Vardi, Amir; Hemi, Rina; Kanety, Hannah; et al.
Abstract: Objective: The Klotho protein family plays important roles in several metabolic pathways. Soluble Klotho has been recently put forward as an antiaging protein, demonstrating renal and cardiovascular protective traits. Cardiopulmonary bypass (CPB) support during cardiac surgery has been implicated in several adverse outcomes in pediatric and adult patients. Our goal was to assess whether serum Klotho levels can be used to predict outcomes in children undergoing cardiac surgery with CPB due to congenital heart defects (CHDs). Methods: This prospective study was conducted on pediatric patients admitted to two Pediatric Cardiac Intensive Care Units, between 2012 and 2018. All patients were born with CHD and underwent corrective surgery with CPB. Sequential blood samples were analyzed by enzyme‐linked immunosorbent assay for soluble Klotho levels at baseline, 2, 6, and 24 h after surgery. The association between Klotho levels and several demographic, intraoperative, and postoperative clinical and laboratory parameters was studied. Results: Twenty‐nine children undergoing cardiac surgery with CPB support were included. Serum Klotho levels were shown to significantly decrease 2 h after surgery and increase to baseline levels after 6 h ( p < .001 and p < .05, respectively). Patients with low Klotho levels 2 h after surgery were at a 32‐fold higher risk for developing postoperative complications ( p = .015, odds ratio < 0.03). Moreover, Klotho levels at each of the four time points were lower in patients who developed postoperative complications. Conclusions: Cardiac surgery with CPB results in a significant decrease of serum Klotho levels 2 h after surgery in pediatric patients with CHDs, which can be used to predict development of postoperative complications in this patient population.